The Influence Of Board Composition On Firm Profitability In Malaysia - Eliezra, Renuka Letchmanan (2024)
Corporate governance regulations have a substantial impact on corporate success and ensure long-term business practices. This study investigates the effect of board composition practices on firm profitability in the Malaysian business environment. This study employs descriptive, diagnostic, and inferential statistical analyses to look into the relationships between a large dataset of corporate governance indicators and firm profitability metrics such as Return on Assets (ROA), board size, ownership concentration, board gender diversity, audit committee size, board meeting frequency, firm size and firm age. The findings show substantial links between board composition procedures and business performance measures. Larger board sizes, concentrated ownership structures, and gender-diverse boards have been found to have a beneficial impact on ROA, emphasizing the importance of effective board governance in driving organizational performance. Furthermore, larger audit committees and more frequent board meetings have been acknowledged as major contributors to enhanced firm profitability through greater financial supervision and strategic decision-making procedures. By controlling for firm size and age, this analysis reveals the contextual details that influence the link between board composition methods and business performance. These findings are useful for policymakers, corporate stakeholders, and practitioners looking to improve corporate governance practices and promote sustainable company growth in Malaysia.